Analysis of the Nominal Value and Collectible Value of the Special Edition 75,000 Rupiah Currency in the Market Mechanism from an Islamic Economic Perspective - Shinta Nuriyah Dwi Astutik; Saifuddin (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This research aims to analyze the phenomenon of trading special edition banknotes with a nominal value of 75,000 rupiah in the market mechanism and assess its compliance with Islamic economic principles. The approach used is qualitative with a type of library research thru descriptive-analytical analysis of various relevant literature. The research results show that special edition currency has undergone a transformation in function from a medium of exchange to a collectible object with collectible value. The value is influenced by factors such as rarity, historical significance, design, and collector preferences, causing market prices to often exceed the nominal value. In the perspective of Islamic economics, this practice is contextual, meaning it can be justified if the money is positioned as a collectible item and the transaction is conducted without elements of riba, gharar, and maisir. However, if it is dominated by speculation, it has the potential to deviate from the principles of Sharia. Therefore, ethical and legal boundaries are necessary to ensure that transactions remain in accordance with the maqasid of Sharia.